Drought resilient Flemingia semialata Roxb. for improving lac productivity in drought prone ecologies - Ghosh, J.; Lohot, V. D.; Ghosal, S.; Singhal, V.; Sinha, N. K. (The Indian Journal of Genetics and Plant Breeding, 2017)
A drought tolerant line of Flemingia semialata (FS-S) hasbeen identified from natural population as a better hostplant for kusmi lac production and summer sustainability.FS-S had significantly higher fresh biomass, dry matter,broodlac and scraplac than local line (FS-L). Photosyntheticrate and stomatal conductance were also higher in FS-Sline and it was fertilizer responsive too. It is more efficientin starch degradation than the local line which ultimatelysupports lac insect development. The high level of totalsugar maintained by FS-S line is due to high chlorophyllcontent including carotenoid. Ascorbate peroxide andcatalase (biochemical indicators for draught tolerance) wasalso higher in selected line